Struktur dan Fungsi Sosial Nyanyian Rakyat Lullaby "Manjujai Anak" Masyarakat Kampuang Tabek - Lilia Zahra Asifa (Lingua Susastra, 2021)
This research was conducted with the aim of describing the structure and social function of the folk song lullaby Manjujai Anak in the Kampuang Tabek Jorong Koto Tingga Nagari Sirukam community. This research is a qualitative research with descriptive methods which was carried out in two stages, namely the data collection stage (interview, record, transcribe, and transliterate the folk song Manjujai Anak from the original language to Indonesian), and the data analysis stage. The data were analyzed using the theory of the study of poetry structure and social functions as used by Herman J. Waluyo (1987), Hasanuddin WS (2002), and Danandjaja (1991). Based on research findings the text structure of the Manjujai Anak song is more precisely formulated into a bound poetry format, which is tied to lines and stanzas. Meanwhile, the social functions found in the text of the song Manjujai Anak are as an inheritance of an oral tradition, children's educational tools, recreational functions, as well as a projection system. The results of this study can reflect the philosophy of life, perceptions, and social behavior of the Kampuang Tabek community, so this research is important to do.